FUNGSI LEMBAGA POSYANDU LANSIA DI DESA KOTO LUBUK JAMBI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Nisa, Ardini Khairun; Widodo, Teguh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research was conducted in Koto Lubuk Jambi Village, Kuantan Mudik District, Kuantan Singingi Regency. This research discusses the Posyandu for the Elderly which was imple-mented to help provide several health services for the elderly in Koto Lubuk Jambi Village, Kuantan Mudik District, Kuantan Singingi Regency to help improve the standard of healthy living and welfare for the elderly. This research aims to (1) determine the function of the el-derly posyandu institution in Koto Lubuk Jambi Village and (2) the effectiveness of elderly activities in Koto Lubuk Jambi Village. This research uses qualitative research methods with 6 informants as research subjects taken based on predetermined criteria. Based on the research results, it can be concluded that there are two functions in the elderly posyandu. These functions are manifest functions and latent functions. Manifest function is a purpose and intentional impact of a social phenomenon. Meanwhile, a latent or hidden function is a func-tion whose abilities and potential are not yet fully manifested or clearly visible, but which emerge and develop in certain conditions and situations. Keywords: Functions of the Posyandu Institution, Elderly, Cadres